Incidência da mastite ovina em criação extensiva e sua relação à dor e variáveis comportamentais - Pellegrini, Manuela Zardin de (2012)
The research evaluated the incidence of mastitis sheep and its relation to pain and behavioral variables in Corriedale herd, handled on native pasture in Rio Grande do Sul. The results were collected in two reviews. The first stage was conducted in December 2010 to determine the incidence of mastitis in multiparous ewes after weaning their lambs. The sheep were submittedto clinical examination and palpation of the udder and classified as scale change in consistency of the udder. No cases of clinical mastitis, but 25% of the herd had chronic mastitis. In the second stage, held in September 2011, was observed behavioral variables in two environments: pen and paddock. Two sheep were evaluated postpartum, which showing udderalteredconsistencyandnormal, respectively.The sheep with udderalteredconsistencyshowed alert behavior pen and paddock. The sheep with normal udder showed higher gregarious behavior and vocalised more often for her lamb. The presence ofnodulesin the udderalteredmaternal-filial behavior the sheep.The indicators of pain were not observed. The clinical mastitis is not a problem in the extensive breeding of sheep, but the presence of chronic mastitis indicates trauma or inflammation without prior treatment.